Laparoscopic management of a giant prostatic utricle: A case report and review of literature (Indian Journal of Case Reports, 2019)
Prostatic utricle is a Mullerian duct remnant with an incidence of 1 %. Excision of utricle is challenging because of the close proximity of seminal vesicle, ejaculatory ducts, bladder, rectum, ureter, and nerve plexus. Here, we report the case of a 23-year-old male presented with complaints of painful terminal hematuria associated with clots along with retrograde ejaculation. The abdominal and local examination was within normal limits. MRI pelvis showed a large non-communicating cystic structure present in the pelvic cavity, compressing posterior wall of the urinary bladder, seminal vesicle, anterior wall of the rectum and also causing left hydroureteronephrosis. After evaluation, the patient was diagnosed with giant prostatic utricle cyst. Laparoscopic excision of prostatic utricle cyst was done successfully. Postoperative period was uneventful and the patient was discharged in satisfactory condition. Laparoscopic excision of prostatic utricle cyst is technically challenging but with acceptable complications and good surgical results.